Interferometric Crossing Orbit Experiment using TerraSAR-X and TanDEM-X - Wollstadt, Steffen; Lopez-Dekker, Paco; Prats, Pau; De Zan, Francesco; Busche, Thomas; Krieger, Gerhard (2011)
The paper discusses quasi repeat-pass SAR interferometry exploiting crossing orbits in order to obtain short revisit times of 1, 5 and 6 days with the TerraSAR-X or TanDEM-X satellite. A special acquisition geometry is necessary for interferometry under crossing orbits to preserve common ground spectra and coherence. This in turn implies limitations for possible acquisition areas. The spectral requirements, the acquisition geometry as well as the geographic limitations are presented. In order to demonstrate the feasibility an experimental acquisition of a test site on the Ronne ice shelf in Antarctica is described and the results are shown. Furthermore, first results w.r.t. glacier surface velocity and topography measurements are presented.